Assessment of Students with Intellectual Disabilities Literacy Condition in Inclusive Context - Anna Augusta Sampaio de Oliveira (Education Policy Analysis Archives, 2015)
The issue of evaluation in the area of intellectual disabilities, an inclusive perspective, is still relatively unexplored in research and educational practice. This study presents results of research on the performance in early literacy. We evaluated 32 students with intellectual disabilities, the 2nd year of elementary school, one of the central regions of São Paulo. The results show learning opportunities as well as difficulties in the area of reading and writing of these students.